Correlating Gastrointestinal Histopathologic Changes to Clinical Disease Activity in Dogs With Idiopathic Inflammatory Bowel Disease. Issue 3 (May 2019) - Allenspach, Karin A.; Mochel, Jonathan P.; Du, Yingzhou; Priestnall, Simon L.; Moore, Frances; Slayter, Michael; Rodrigues, Aline; Ackermann, Mark; Krockenberger, Mark; Mansell, Joanne; ,; Luckschander, Nicole; et al.
Prior studies have failed to detect a convincing association between histologic lesions of inflammation and clinical activity in dogs with inflammatory bowel disease (IBD). We hypothesized that use of a simplified histopathologic scoring system would improve the consistency of interpretation among pathologists when describing histologic lesions of gastrointestinal inflammation. Our aim was to evaluate the correlation of histopathologic changes to clinical activity in dogs with IBD using this new system. Forty-two dogs with IBD and 19 healthy control dogs were enrolled in this retrospective study. Endoscopic biopsies from the stomach, duodenum, ileum, and colon were independently scored by 8 pathologists. Clinical disease activity was scored using the Canine Inflammatory Bowel Disease Activity Index (CIBDAI) or the Canine Chronic Enteropathy Clinical Activity Index (CCECAI), depending on the individual study center. Summative histopathological scores and clinical activity were calculated for each tissue (stomach, duodenum, ileum, and colon) and each tissue histologic score (inflammatory/morphologic feature). The correlation between CCECAI/CIBDAI and summative histopathologic score was significant ( P < .05) for duodenum ( r = 0.42) and colon ( r = 0.33). In evaluating the relationship between histopathologic scores and clinical activity, significant ( P < .05) correlations were observed for crypt dilation ( r = 0.42), lamina propria (LP) lymphocytes ( r = 0.40), LP neutrophils ( r = 0.45), mucosal fibrosis ( r = 0.47), lacteal dilation ( r = 0.39), and villus stunting ( r = 0.43). Compared to earlier grading schemes, the simplified scoring system shows improved utility in correlating histopathologic features (both summative histology scores and select histologic scores) to IBD clinical activity.